A study of Penang Peranakan Hokkien - Boon Seong Teoh; Beng Soon Lim; Liang Hye Lee (Journal of Modern Languages)
This paper attempts to classify the loan words in Penang Peranakan Hokkien, a creole variety of Hokkien, according to classifications as objects and formal grammatical categories. The study is based on a word list of about 400 Malay words taken from a Penang Peranakan family and commonly found in this variety. The paper concludes with some observations of current trends in Penang Peranakan Hokkien.